Diagnosis and treatment of mandibular extraoral sinus of periodontal origin in a 9-year-old boy: A case report - Ozdemir A; Guven G; Dilsiz A; Sencimen M (Wolters Kluwer Medknow Publications, 2008)
Cutaneous sinus tract of dental origin is the commonest of the many types of sinus tracts that are formed on the face and neck. Cutaneous sinus tracts may originate from local chronic osteomyelitis (Garre′s osteomyelitis). Although the etiological factor is usually periapical infection, they are seldom of periodontal origin. Conventional periapical and panoramic roentgenograms are generally insufficient for diagnosis and treatment planning of cutaneous sinus tracts of periodontal origin. In the present case, computed tomography was used for diagnosis, and osteomyelitis was managed by periodontal treatment.